THE EFFECT OF A VISUAL TRAINING CURRICULUM TO DEVELOP THE LEVEL OF THROWING AMONG ADVANCED PLAYERS WITH AIR PISTOLS - Esraa Hashem Jayan; Amin Khazal Dhi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The research consists of four chapters and the aim of the study is to identify the effect of exercise used to develop the correction pistol antenna accuracy, the experimental research sample totaling (5) archers from players exert youth team shooting was carried out the experiment on the shooting hall in the Iraqi Central Union, from 02/01/2020 until 01/03/2020, was used experimental method in the research was the use of tests to measure the correction pistol antenna accuracy, and after the completion of the experiment was calculated results statistically by a program (spss), and the results were significant differences between pre and post tests and for the post-test, and concluded that the researcher that exercises used positively affected in improved correction accuracy, the researcher recommended the necessity of using new methods and techniques for the development of pistol shooting accuracy antenna.